Conflictos entre principios: descripción y crítica de la teoría especificacionista - García Yzaguirre, José Víctor (2019)
Through the present work we intend to reconstruct and criticize José Juan Moreso’s proposal of contextualist universalist specificationism as a method of conflict resolution between principles with the aim of showing its methodological problems and limits. We will focus our approximation as to whether it does not produce norms that are not defeasible and if it provides an adequate mechanism for the selection of properties relevant to the construction of antecedents of norms.